Analysis of Completeness in Library Facilities and Infrastructure in Supporting Student's Reading Interest at MTs Al-Ittihad Aeknabara - Ersa Ananda Sirait; Emeliya Sukma Dara Damanik; Esi Audya Usaida; Mawaddah Afifah Husna Rambe (English Teaching and Linguistics Journal (ETLiJ), 2022)
This study focused on the facilities and infrastructure contained in the school library of MTS Al-IttihadAeknabara to see the effect of facilities and infrastructure in supporting students' reading interest. This study uses data collection techniques which are carried out by observation or direct observation to the location of observation. The findings show that the facilities and infrastructure in the MTS Al-Ittihad library room are quite complete which can support students' reading interest. The library room will be equipped with reading chairs and reading tables that make it easier for students to read books in the library.This study describes the analysis of the completeness of the facilities and infrastructure contained in the school library of the MTS Al-Ittihad.